Formulation and Evaluation of Herbal Soap Containing Ocimum tenuiflorum (Tulsi) for Enhanced Skin Health: Research Article (Journal of Pharma Insights and Research, 2024)
This study aimed to develop and evaluate a herbal soap formulation containing Ocimum tenuiflorum (Tulsi) and other natural ingredients to promote skin health. The soap was prepared using the double boiling method, incorporating Tulsi powder, turmeric, aloe vera gel, almond oil, rose water, and lavender essential oil into a glycerin soap base. The formulation process and ingredient selection were based on the therapeutic properties of each component, with a focus on antibacterial, anti-inflammatory, and moisturizing effects. The resulting soap was subjected to various evaluation parameters, including organoleptic properties, physical characteristics such as foam retention, foamability, and pH, as well as skin sensitivity and irritation tests. The herbal soap demonstrated favorable characteristics in terms of appearance, odor, and skin compatibility. Its natural composition offers potential advantages over conventional soaps, including the absence of harsh chemicals and the presence of active phytochemicals that may benefit skin health. This study contributes to the growing body of research on natural cosmetic formulations and highlights the potential of herbal ingredients in personal care products. Further research, including clinical trials, is recommended to fully elucidate the efficacy and long-term benefits of this herbal soap formulation for various skin types and conditions